2021
DOI: 10.1167/tvst.10.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography Quality Across Three Multicenter Clinical Studies of Diabetic Retinopathy

Abstract: Purpose To explore optical coherence tomography angiography (OCTA) quality and associated factors in multicenter clinical studies. Methods OCTA scans were obtained from participants with diabetic retinopathy from three DRCR Retina Network clinical studies using the Optovue AngioVue and ZEISS AngioPlex. Macular (3 × 3 mm and 6 × 6 mm) and optic nerve scans were captured. Quality was assessed by the Casey Reading Center. Scans were considered “poor” if the signal strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The issue of image quality is especially important for OCTA evaluation, as OCTA is burdened with the problem of artifacts. Most reports confirmed the impact of poorer-quality OCTA scans on the measurement of vascular parameters, especially for repeated measurements [ 34 , 35 , 36 ]. Some authors directly recommend OCTA scan quality as high as 9/10 for comparative analysis [ 37 ].…”
Section: Discussionmentioning
confidence: 90%
“…The issue of image quality is especially important for OCTA evaluation, as OCTA is burdened with the problem of artifacts. Most reports confirmed the impact of poorer-quality OCTA scans on the measurement of vascular parameters, especially for repeated measurements [ 34 , 35 , 36 ]. Some authors directly recommend OCTA scan quality as high as 9/10 for comparative analysis [ 37 ].…”
Section: Discussionmentioning
confidence: 90%
“…This will provide image reproducibility, will make validation of diagnosis and treatment outcomes possible, and will make monitoring of changes over time more reliable and uniform. Image quality control mechanisms are also necessary for the effective use of OCT-A in DR evaluation and multicenter clinical trials [105]. Greig, Duker, and Waheed [106] offered a guide for a more effective OCT-A image analysis by assessing the (1) en face OCT-A image, (2) corresponding B-scans with vessel flow overlay, and (3) structural en face image for each retinal slab using a step-by-step method.…”
Section: The Reading Center Perspective: Manual Versus Automatic Evaluation and Agreement On Protocols In Clinical Trialsmentioning
confidence: 99%
“…Large-scale observational studies offer the opportunity to explore the utility of novel non-invasive imaging modalities. A number of currently running clinical trials have included exploratory analyses with wide-field OCT, OCTA and colour fundus photography and we await the results with interest [74][75][76]. In a recent multicentre, head-to-head, real-world validation study of seven automated AI DR screening systems, the algorithms showed significant performance differences; for example, one system missed 25% of cases of PDR.…”
Section: Validation In Prospective Observational Studies and Randomised Clinical Trialsmentioning
confidence: 99%